Comparison of team-based learning vs. lecture-based teaching with small group discussion in a master's degree in nursing education course. (October 2021) - Xue, Hui; Yuan, Hua; Li, Guichen; Liu, Jiamei; Zhang, Xiuying
Abstract: Background: The high student-to-faculty ratio is an obstacle in the reform of teaching methods in master's programmes of nursing education in China. Though Kim's study showed that team-based learning (TBL) can be implemented in high student-to-faculty ratio classes, it is still a challenge for students accustomed to the traditional didactic lecture (TDL) teaching method, and the lack of an inclusive design model has restricted the effective application of TBL. Objective: To compare the effect of TBL on postgraduate nursing students with lecture-based teaching with small group discussion (LBTWSGD) and to clarify key factors to promote the effective application of TBL. Methods: A quasi-experimental study design. We selected 27 unbiased participants in the applied LBTWSGD group and 48 participants in the applied TBL group and conducted questionnaire surveys at the last day of the course which lasted for 10 weeks. Students' self-directed learning ability was assessed by the Self-Directed Learning Instrument (SDLI), classroom engagement was assessed by the Self-Report of Engagement Measure (SREM), and students' evaluation of the teaching experience was assessed by the Student Evaluation of Teaching and Units (SETU). A difference analysis between the two groups was performed by the SETU. The mean and standard deviation of each tool were calculated and compared between the two groups. Results: The study determined that compared to LBTWSGD, TBL significantly improved students' self-directed learning ( p  < 0.01) and classroom engagement ( p  < 0.05). The scores for 6 of 9 items in the SETU were significantly higher in the TBL group than in the LBTWSGD group. Conclusions: The TBL teaching method can effectively improve nursing students' self-learning ability and classroom engagement through effective teacher feedback, discussion, and communication. The same clear and definite reading assignments in TBL can help students obtain effective teacher feedback and form effective discussions and communication.